MEANING OF PROPOSING DIVORCE IN TUBAN REGENCY OF EAST JAVA (Matrilocal Residence in Proposing Divorce) - Ulin Na`mah (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2015)
The availability of nafkah (money given by husband to his wife for household expenses) in family life often becomes a source of conflict. Moreover, nafkah often becomes a reason for husband and wife for divorce. This is due to the obligation for providing nafkah is relied on husband (man) rather than wife (woman). Yet, on the one hand, “nafkah relied on husband” is often used by husband to powerfully control over his wife. On the other hand, in a culture of matrilocal residence (in wife’s home with her parents), “nafkah relied on husband” can be also used by wife to powerfully control her husband  and this becomes a means for woman to subordinate and oppress her husband. Furthemore, for both husband or wife, “nafkah relied on husband” may often becomes a trigger to divorce. Therefore, it is important to redefine such strict division of gender role and contextually give more priority to equality in gender role in households life.Copyright (c) 2015 by Al-Ihkam. All right reserved DOI : 10.19105/al-ihkam.v10i2.715